Uma investigação metaética a partir do conceito de forma(s) de vida em Wittgenstein - Boeira, Jéssica Machado (My University, 2026)
The present work consists of a conceptual investigation whose aim is to analyze, from a metaethical perspective, the concept of Form(s) of Life (Lebensform) in the philosophy of Ludwig Wittgenstein. Although this is a secondary concept in the author's thought, it acquires particular importance in the Philosophical Investigations and also maintains relevant connections with assumptions previously established in the Tractatus Logico-Philosophicus. Throughout the contemporary philosophical tradition, the notion of form of life has been interpreted in different ways, especially with regard to its implications for morality and for the epistemological status of moral judgments. On the one hand, there is an interpretation that emphasizes the multiplicity of forms of life, understood as expressions of different sociocultural contexts, which leads to a pluralist and relativist conception of morality, often associated with a non-cognitivist ethical epistemology. On the other hand, there is an interpretation that privileges the human form of life as a fundamental category, in contrast to other possible forms of life, allowing morality to be conceived in non-relativist terms and supporting a cognitivist moral epistemology. The dissertation aims to critically reconstruct these two interpretations, examining their assumptions and metaethical consequences, as well as their textual adequacy to Wittgenstein's works. On the basis of this analysis, it is argued that the interpretation which takes the human form of life as the foundation of linguistic and normative practices proves to be more consistent with Wittgenstein's philosophy, insofar as it allows for an understanding of moral objectivity without recourse to metaphysical foundations, while also avoiding its reduction to cultural relativism. It is thus concluded that the concept of form of life plays a decisive role in the possibility of a non-metaphysical moral objectivity within Wittgenstein's philosophy. [resumo fornecido pelo autor]
O presente trabalho consiste em uma investigação conceitual que tem por objetivo analisar, sob uma perspectiva metaética, o conceito de Forma(s) de Vida (Lebensform) na filosofia de Ludwig Wittgenstein. Trata-se de um conceito secundário no pensamento do autor, mas de uma importância particular nas Investigações Filosóficas, que também apresenta vínculos relevantes com pressupostos já estabelecidos previamente no Tractatus Logico-Philosophicus. Ao longo da tradição filosófica contemporânea, a noção de forma de vida tem sido interpretada de maneiras distintas, sobretudo no que diz respeito às suas implicações para a moralidade e para o estatuto epistemológico dos juízos morais. De um lado, destaca-se uma interpretação que enfatiza a multiplicidade das formas de vida, compreendidas como expressões de diferentes contextos socioculturais, o que conduz a uma concepção pluralista e relativista da moral, frequentemente associada a uma epistemologia ética de caráter não cognitivista. De outro lado, encontra-se uma interpretação que privilegia a forma de vida humana como categoria fundamental, em contraste com outras possíveis formas de vida, permitindo pensar a moralidade em termos não relativistas e sustentando uma epistemologia moral de caráter cognitivista. A dissertação propõe-se a reconstruir criticamente essas duas interpretações, examinando seus pressupostos e suas consequências metaéticas, bem como sua adequação textual às obras de Wittgenstein. A partir dessa análise, defende-se que a interpretação que toma a forma de vida humana como fundamento das práticas linguísticas e normativas mostra-se mais consistente com o pensamento wittgensteiniano, ao permitir compreender a objetividade da moral sem recorrer a fundamentos metafísicos, mas também sem reduzi-la ao relativismo cultural. Conclui-se, assim, que o conceito de forma de vida desempenha um papel decisivo na possibilidade de uma objetividade moral não metafísica no interior da filosofia de Wittgenstein. [resumo fornecido pelo autor]
Keywords: Wittgenstein, Ludwim, 1889-1951; Metaética; Relatividade; Ética; Conduta; Metaethics; Relativity; Ethics; Conduct of life